Pengaruh Pemberian Tanah Mineral Dan Aerasi Pada Tanah Gambut Yang Disawahkan Terhadap Pertumbuhan dan Produksi Tanaman Padi (Oryza sativa. L) - David A Sibagariang; Wawan '; Husna Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the proper dose of minerals oil as a material amelioranton peat soil and aeration delivery on peat land planting medium to support the grow thand yield ofrice. The research was conducted at the Experimental Station of the Faculty of Agriculture, University of Riau in May until September 2012. This study conducted experiments using completely randomized design with 2 factor sand three replications. The first factoris the provision of minerals oil with 4levels: TM0=0g/pot, TM1=280g/pot, TM2=560g/pot, TM3=840g/pot. The second factoris Aeration with 2levels: with out aeration and A0=A1=Byproviding aeration. The result show that mineral and aerated soil factors significantly affected all parameters of observation. The interaction between the two treatments also significantly affected all parameters ofobservation. Key words: rice, peat, mineralsoil, aeration